Challenges, Resilience and Career Path Among LGBTQ Students: Input to a Transformative Support Program in the University of Rizal System - Francisco, Bernadette (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the challenges, academic resilience, and career paths of LGBTQ students at the University of Rizal System (URS) and developed a transformative support program based on the findings. Guided by Minority Stress Theory and Social Cognitive Career Theory, the study employed a mixed-methods research design integrating quantitative and qualitative approaches to provide a comprehensive understanding of the experiences of LGBTQ students. The respondents were LGBTQ students enrolled across the ten URS campuses during the School Year 2023–2024, selected through voluntary sampling. Data were gathered using a researcher-made questionnaire, the Academic Resilience Scale (ARS-30), the Brief Resilience Scale, and semi-structured interviews. Descriptive statistics, inferential analyses, and thematic analysis were utilized to analyze the data. The findings revealed that LGBTQ students experienced moderate levels of challenges, particularly in discrimination, harassment, mental health concerns, access to resources, safety, legal and policy issues, and campus life. Despite these challenges, the respondents demonstrated a generally satisfactory level of academic resilience characterized by perseverance, reflective and adaptive help-seeking behaviors, and the capacity to recover from adversity. However, negative affect and emotional responses remained areas of concern, indicating the need for stronger psychosocial support. The study further showed significant differences in the extent of challenges and resilience across selected demographic variables and established a significant relationship between challenges encountered and academic resilience. Qualitative findings emphasized the importance of inclusive institutional policies, supportive peer and faculty relationships, accessible counseling services, and affirming campus environments in fostering resilience and informed career decision-making. Based on the results, the study proposed a transformative support program aimed at strengthening mental health services, career guidance, inclusive policies, and student support mechanisms to promote the academic success, well-being, resilience, and career development of LGBTQ students within the University of Rizal System and other higher education institutions committed to inclusive and equitable educational practices.